Efficiency of double fixed combined therapy in patients with arterial hypertension and associated thyrotoxicosis after one year of treatment - Tseluyko, Vira; Korchagina, Daria (ScienceRise: Medical Science, 2020)
The aim: to evaluate the effectiveness of different fixed double antihypertensive combinations based on the results of outpatient monitoring of arterial pressure and to analyze their effect on central arterial pressure and cardiac remodeling in patients with arterial hypertension and thyrotoxicosis. Materials and methods: patients with hypertension and TT who were included in the study were divided into groups using the blind envelope method with compensated TT: patients of group 1 were prescribed a fixed combination of perindopril with indapamide, group 2 - a combination of perindopril with amlodipine. Patients with uncompensated TT were prescribed a combination of bisoprolol with perindopril. The groups were statistically comparable in terms of age, duration of AH and TT, SBP and DBP levels. The observation of the patients lasted 12 months. After a year of follow-up, AMAD and EchoCG were performed in order to study AHT in patients with hypertension and TT. The patients were consulted by a cardiologist and endocrinologist. Results: After 6 months of treatment, 8 (16 %) patients were excluded from the study, of which 6 (75 %) due to the need for surgical treatment and did not achieve euthyroidism, 2 (25 %) due to the need for antiarrhythmic therapy. Studied double fixed combinations effectively reduce blood pressure (BP) according to the results of ambulatory blood pressure monitoring (ABPM). Conclusions: The fixed combination of perindopril with indapamide, perindopril with amlodipine, bisoprolol with perindopril provided a decrease in both blood pressure according to ABPM results and central pressure, however, this was not accompanied by a significant improvement in the structural and functional state of the heart